TECHNOLOGIES OF FORMING MUSICAL CREATIVITY OF SCHOOL CHILDREN - E. Qobilova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about improving the technologies of forming the musical creativity of preschool children by means of Uzbek folk musical instruments.